The legal framework to manage chemical pollution in India and the lesson from the Persistent Organic Pollutants (POPs) - Sharma, Brij Mohan; Bharat, Girija K; Tayal, Shresth; Nizzetto, Luca; Larssen, Thorjørn (The Science of the total environment, 2014)
India's rapid agro-economic growth has resulted into many environmental issues, especially related to chemical pollution. Environmental management and control of toxic chemicals have gained significant attention from policy makers, researchers, and enterprises in India. The present study reviews the policy and legal and non-regulatory schemes set in place in this country during the last decades to manage chemical risk and compares them with those in developed nations. India has a large and fragmented body of regulation to control and manage chemical pollution which appears to be ineffective in protecting environment and human health. The example of POPs contamination in India is proposed to support such a theory. Overlapping of jurisdictions and retrospectively approached environmental policy and risk management currently adopted in India are out of date and excluding Indian economy from the process of building and participating into new, environmentally-sustainable market spaces for chemical products. To address these issues, the introduction of a new integrated and scientifically-informed regulation and management scheme is recommended. Such scheme should acknowledge the principle of risk management rather than the current one based on risk acceptance. To this end, India should take advantage of the experience of recently introduced chemical management regulation in some developed nations.
Keywords: environmentální politika; Persistent Organic Pollutants (POPs); Indie; REACH; Environment Policy; Chemical Management; Environmental Monitoring; Environmental Pollution; Toxic Chemicals; znečištění životního prostředí; látky znečišťující životní prostředí; monitorování životního prostředí; Environmental Pollutants; Environmental Policy; organické látky; Organic Chemicals; India; Risk Assessment; hodnocení rizik